Effects of Irrigation Regimes and Rice Varieties on Methane Emissions and Yield of Dry Season Rice in Bangladesh - Habib, Muhammad Ashraful; Islam, S. M. Mofijul; Haque, Ashraful; Hassan, Lutful; Ali, Zulfiker; Nayak, Swati; Dar, Manzoor Hussain; Gaihre, Yam Kanta (MDPI, 2023)
Adoption of the right rice variety and water-saving irrigation method could reduce greenhouse gas (GHG) emissions in lowland rice cultivation. A study was conducted at the research farm of Bangladesh Agricultural University, Mymensingh, Bangladesh, in 2019 during the Boro (dry) season to determine the impacts of different rice varieties (BRRI dhan29, BRRI dhan47, BRRI dhan69, Binadhan-8, Binadhan-10, and Binadhan-17) on methane (CH4) emissions under two irrigation methods, i.e., alternate wetting and drying (AWD) and continuous flooding (CF). The treatments were laid out in a split-plot design, considering water regime as the main plots and rice variety as the sub-plots. The emission rates of CH4 were determined by collecting air samples using the closed chamber technique and measuring the concentrations using a gas chromatograph. CH4 emission rates varied with the growth and development of the rice varieties. The lowest cumulative CH4 emission rate was observed in Binadhan-17, particularly under AWD irrigation. Across the rice varieties, AWD irrigation significantly reduced the cumulative CH4 emissions by about 35% compared with CF. No significant variation in rice yield was observed between AWD (5.38 t ha−1) and CF (5.16 t ha−1). This study suggests that the cultivation of Binadhan-17 under AWD irrigation could be effective at reducing the carbon footprint of lowland rice fields.